DMSO as a mobile phase additive enhances detection of ubiquitination sites by nano‐LC‐ESI‐MS/MS. (19th January 2018) - Doellinger, Joerg; Grossegesse, Marica; Nitsche, Andreas; Lasch, Peter
Abstract: Large‐scale detection of ubiquitination sites in whole cell proteomes using nano–liquid chromatography coupled to tandem mass spectrometry is a well‐established technique that has deepened the understanding of protein degradation processes in eukaryotic cells. Ubiquitination sites are usually identified by detection of Lys‐ɛ‐Gly‐Gly (K‐ɛ‐GG)‐remnant peptides, which are generated by tryptic digestion of proteomes. We show in this application note that dimethyl sulfoxide addition to the liquid chromatography mobile phase enhances identification rates of K‐ɛ‐GG peptides by more than 100% due to an increase of peptide signal intensities. The gain in the number of ubiquitination site identifications exceeds by far the gain that has been published for other posttranslational modifications, namely, phosphorylation and acetylation.